Fishery resilience in Covid-19 post-pandemic era: sustainable environmental approach for potential challenges in Asia - John, Akbar; Chowdhury, Ahmed Jalal Khan; Munir, Mohammad Bodrul; Abdullah, Rose; Zainal Abidin, Zaima Azira; Nordin, Noor Faizul Hadry (Springer Nature, 2025)
The COVID-19 pandemic has had a substantial impact on the global fishery industry, causing widespread disruption to supply chains and market demand. This has led to significant economic challenges for fishing communities, particularly in developing countries where fishing is a major source of livelihood. In the challenge of the pandemic, it is important to consider ways to build resilience in the fishery industry to ensure its continued viability in the time to come. One approach to achieving fishery resilience is to focus on sustainable fishing practices. This involves implementing measures to minimize the impacts of fishing on the natural aquatic environment by reducing human intervention such as bycatch and protecting critical habitats. Additionally, investment in aquaculture can help to reduce dependence on wild-capture fishing and provide a more controlled and sustainable source of fish for human consumption. Another important aspect of building fishery resilience is improving supply chain management. This involves establishing more efficient and effective processes for catching, processing, and distributing fish and seafood products, to minimize waste and ensure that products reach markets in a timely manner. Improving supply chain management can also help to reduce the economic impacts of the pandemic by ensuring that fish and seafood products are available for sale even in the face of market disruptions. In conclusion, the COVID-19 pandemic has had a profound impact on the global fishery industries especially Asia–Pacific region, highlighting the need for greater resilience in this critical sector. By means of focusing on sustainable fishing practices and improving supply viability for generations to come chain management, the industry can develop a more sustainable and resilient future, ensuring its viability for generations into the near future.